Ethanol Extract of Rosa damascena Effects the Kidney Crystal Deposit in Wistar Rats - Darwin,; Ginting, Sahna Ferdinand; Chiuman, Linda; Ginting, Chrismis Novalinda (British Journal of Healthcare and Medical Research, 2022)
This research aims to show that the elixir of the ethanol extract of Rosa damascena on the solubility of urine calcium oxalate crystal in Wistar rats. The experimental rats were divided into six groups: the control group (K0); ethylene glycol 0.75% and ammonium chloride 2% as an inducer (K-); inducer and Batugin elixir (K+); inducer and the elixir of the ethanol extract of Rosa damascena 250 mg/kg body weight (P1); 500 mg/kg body weight (P2) and 1000 mg/kg body weight (P3). The treatment was carried out for 28 days by examining urine crystals; urine pH was carried out on days 14 and 28, rat body weight measurements were carried out on days 14 and 28. At the end of the treatment period, the rats were necropsied using a combination of ketamine xylazine, and their kidneys were taken. Results showed that the elixir of ethanol extract of Rosa damascena was able to dissolve calcium oxalate crystals with the best dose of 500 mg/kg BW based on the weight gain, decreased kidney weight ratio, decreased concentration of creatinine and urea, and decreased number of kidney crystal deposits.